Migration, Culture and Identity Making Home Away - Shamma, Yasmine; Ilcan, Suzan; Squire, Vicki; Underhill, Helen (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is about homemaking in situations of migration and displacement. It explores how homes are made, remade, lost, revived, expanded and contracted through experiences of migration, to ask what it means to make a home away from home. We draw together a wide range of perspectives from across multiple disciplines and contexts, which explore how old homes, lost homes, and new homes connect and disconnect through processes of homemaking. The volume asks: how do spaces of resettlement or rehoming reflect both the continuation of old homes and distinct new experiences? Based on collaborations with migrants, refugees, practitioners and artists, this book centres the lived experiences, testimonies, and negotiations of those who are displaced. The volume generates appreciation of the tensions that emerge in contexts of migration and displacement, as well as of the ways in which racial categories and colonial legacies continue to shape fields of lived experience. Yasmine Shamma is Associate Professor of Modern and Contemporary English Literature, University of Reading, UK. Suzan Ilcan is Professor of Sociology at the Department of Sociology and Legal Studies, University of Waterloo and the Balsillie School of International Affairs, Canada. Vicki Squire is Professor of International Politics, Department of Politics and International Studies, University of Warwick, UK. Helen Underhill is a Researcher in the School of Architecture, Planning, and Landscape at Newcastle University, UK.
1. Making Home Away: Introduction to the Collection -- 2. Watfa' Speaks -- 3. Refugee-Refugee Hosting as Home in Protracted Urban Displacement: Sudanese Refugee Men in Amman, Jordan -- 4. Archiving Displacement and Identities: Recording Struggles of the Displaced Re/making Home in Britain -- 5. Archival Home Making: Reference, Remixing and Reverence in Palestinian Visual Art -- 6. Collecting: The Migrant's Method for Home-making -- 7. Syrian Experiences of Remaking Home: Migratory Journeys, State Refugee Policies, and Negotiated Belonging -- 8. Making Home in the Earth: Ecoglobalism in the Camps -- 9. Home is Like Water.
Keywords: Emigration and immigration-Government policy; Emigration and immigration; Culture-Study and teaching; Literature, Modern-20th century; Literature, Modern-21st century; Anthropology; Migration Policy; Human Migration; Cultural Studies; Contemporary Literature; Anthropology